Two Cases of an Enigmatic Entity: Kikuchi’s Disease - Şahin, Sevinç; Seçkin, Selda (International Journal of Pathology, 2018)
Background: Kikuchi’s disease [KD] is a self-limited rare disorder characterized by necrotizing lymphadenopathy inespecially women with a mean age of 27.4 years. It mostly arises in the posterior cervical triangle. Lympadenopathy may beaccompanied by fever, chills, myalgias, arthralgias, splenomegaly, hepatomegaly and/or skin rashes. KD’s etiology isunknown, and it is commonly misdiagnosed as lymphoma. Herein, we present two cases of KD consulted to our institute intwo weeks period.Case Presentations: The first case was a 41 year-old male presented with a posterior cervical lymphadenopathy of2x1.7x1 cm in size. The second case was a 33 year-old female presented with a left axillary lymphadenopathy of 1.5x1x1 cm insize. The paraffin blocks of lymph node biopsies were evaluated. Similar findings were detected in both cases, and thediagnoses of KD were reached microscopically. There were multiple foci of patchy necrosis. Necrotic foci were composed ofnuclear dusts phagocytosed by numerous histiocytes with crescentic nuclei that were positive for myeloperoxidaseimmunohistochemically. Numerous immunoblasts with atypical nuclei were detected.Discussion: It should be noted that discriminating KD from systemic lupus erytematosus [SLE], cat-scratch disease, andparticularly some lymphomas showing necrosis in the lymph nodes is usually difficult. A brief summary about theclinicopathological characteristics and clues about the differential diagnosis of KD are given in this report with twodemonstrative cases in order to contribute a better understanding of this rare enigmatic entity.